PENGARUH KECERDASAN INTELEKTUAL, EMOSIONAL, SPIRITUAL DAN MOTIVASI BELAJAR TERHADAP PEMAHAMAN AKUNTANSI - Azis Rifaldi Subagja Pratama; Asep Qustolani; Yogi Ginanjar (Prosiding SEMANIS: Seminar Manajemen Bisnis, 2023)
There is a difference in the level of understanding of accounting among students of the Accounting Study Program, Faculty of Economics and Business, Majalengka University, between the survey results of the student's GPA scores being considered good but inversely proportional to the survey results. This study aims to determine how much influence intellectual, emotional, spiritual and learning motivation have on understanding accounting studies in Students of the Accounting Study Program, Faculty of Economics and Business, University of Majalengka. The population in this study were Students of the Accounting Study Program, Faculty of Economics and Business, Majalengka University. The sampling technique used in this study was purposive sampling where in determining the sample with certain considerations, the number of samples in this study were 58 respondents. Testing the research instrument was carried out by testing the validity and reliability. The data analysis technique uses descriptive analysis and verification through the classical assumption test, multiple linear regression analysis, determination analysis, model feasibility test (F test) and hypothesis testing t test. The analytical tool in this study used the SPSS 25 program. The results showed that intellectual, emotional, and learning motivation had an effect on accounting understanding, spiritual intelligence had no effect